PENINGKATAN KETERAMPILAN MENULIS TEKS NARASI MELALUI MODEL PBL BERBANTUAN MEDIA GAMBAR BERSERI PADA SISWA KELAS V SDN 075/VII KASANG MELINTANG - Susi Ulandari; Puput Wahyu Hidayat (STKIP Subang, 2026)
This Classroom Action Research (CAR) aimed to improve the narrative text writing skills of Grade V students at SDN 075/VII Kasang Melintang through the Problem-Based Learning (PBL) model assisted by serial picture media. The study was conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The subjects were 16 Grade V students. Data were collected through written tests, observation sheets, and documentation. The results showed a significant improvement across both cycles. The average class score increased from 56.4 in the pre-cycle to 66.9 in Cycle I, and further rose to 78.8 in Cycle II, surpassing the minimum completeness criterion of 75.0. The percentage of students achieving mastery learning also increased from 37.5% (pre-cycle) to 62.5% (Cycle I) and 87.5% (Cycle II). It is concluded that the PBL model assisted by serial picture media effectively improves narrative text writing skills, particularly in aspects of content, organization, vocabulary, language use, and mechanics.